Common NOD2/CARD15 variants are not associated with susceptibility or the clinicopathologic characteristics of sporadic colorectal cancer in Hungarian patients - Lakatos, Peter Laszlo (BioMed Central, 2007)
BACKGROUND: Epidemiological observations suggest that cancer arises from chronically inflamed tissues. Inflammatory bowel disease (IBD) is a typical example as patients with longstanding IBD are at an increased risk for developing colorectal cancer (CRC) and mutations of the NOD2/CARD15 gene increase the risk for Crohn's disease (CD). Recently, NOD2/CARD15 has been associated with a risk for CRC in some studies, which stemmed from ethnically diverse populations. Our aim was to identify common NOD2/CARD15 mutations in Hungarian patients with sporadic CRC. METHODS: A total of 194 sporadic CRC patients (m/f: 108/86, age at diagnosis of CRC: 63.2 ± 9.1 years old) and 200 healthy subjects were included. DNA was screened for SNP8, SNP12 and SNP13 NOD2/CARD15 mutations by denaturing-HPLC and confirmed by direct sequencing. RESULTS: NOD2/CARD15 mutations were found in 28 patients (14.4%) and in 23 controls (11.5%, p = NS). Allele frequencies for SNP8/R702W (1.8% vs. 1.5%) SNP12/G908R (1.8% vs. 1.8%) and SNP13/3020insC (3.6% vs. 2.5%) were also not statistically different between patients and controls. The clinicopathologic characteristics of CRC patients with or without NOD2/CARD15 mutations were not significantly different. CONCLUSION: Our results suggest that common NOD2/CARD15 mutations alone do not contribute to CRC risk in the Hungarian population.